The Implementation of Communicative Language Teaching (CLT) Approach in Efl Classes; A Case Study on The Border Of Indonesia – Malaysia - Muhammad Nurikhsan Ridwan; Ramli; Udi Samanhudi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The position of English in Indonesia as a foreign language requires teachers to be more creative in using the right approach in teaching EFL classes. One approach teachers widely apply is the CTL approach because it is considered by them to combine the four skills in English, namely listening, speaking, and reading. and writing. However, the application of the CLT approach depends more or less on the character of the class being taught and is influenced by several factors, including the geographical location of an area where Sebatik Island is geographically located on the border of Indonesia and Malaysia. It makes the application of the CLT approach may be different from other areas find borders with other countries. This research aims to qualitatively describe the implementation of the CLT approach in the classroom by English teachers on Sebatik Island and the challenges they face in implementing it. The research method used is descriptive qualitative with a case study approach. Data collection methods were collected through observation, interviews, Focus Group Discussions (FGD), and triangulation involving four respondents from several junior high schools on Sebatik Island. The data collected was then analyzed using the Miles and Huberman interactive analysis model consisting of three activity streams that co-occurred: data reduction, data presentation, and conclusion. From the data analysis using the model, the geographical location of Sebatik Island, which directly borders Malaysia, positively contributes to students' communication skills. However, the implementation of the Communicative Language Teaching (CLT) approach by teachers on Sebatik Island is not free from several challenges, namely the lack of understanding among some teachers regarding the importance of this approach in learning English, the provision of supporting facilities, support from various parties including school principals and Government Agencies Education, as well as the political dynamics in the regions, which tend to be unproductive in developing teacher competency.